Tradición y modernidad del concepto de Reforma Agraria - Paniagua Mazorra, Ángel (Estudios humanísticos. Geografía, historia y arte, 1993)
The agrarian reform have been enclosed with a complex theory model. There are differents focus and confuse terminology. This work want to contribute a synthesis, it insist the points of convergence and divergence. So, it analyse the rural development, agrarian reform and the importance the social context and the role of the state.